Use of Platelet rich plasma in persistent olfactory dysfunction after COVID-19: a prospective study - Sousa,Francisco Alves de (2023)
Abstract Introduction: A promising technique to treat persistent olfactory impairment has recently been explored: platelet rich plasma (PRP) injection into the olfactory mucosa. Objectives: This study aimed to determine efficacy, safety, and feasibility of a new PRP injection protocol in treating persistent COVID-19 induced olfactory dysfunction (pCIOD). Material and Methods: Patients with pCIOD lasting for ≥ 12 months were enrolled. All patients had previously performed olfactory training and adjuvant therapy without achieving substantial improvement. Olfactory perception threshold (OPT) and visual analog scale (VAS) were measured at baseline, one month and three months after injection. Results: Twenty patients were enrolled. There was a significant change in OPT after injection (mean baseline OPT: 4.36 ± 1.6 versus 1-month after injection: 6.9 ± 2.6, p = 0.012 versus 3-months after injection: 7.2 ± 2.8, p =0.009). No severe complications were reported. Conclusions: Single-site PRP injection into the olfactory mucosa is a novel, safe and effective approach that may enhance olfactory recovery in pCIOD patients.